Customer Relationship Management, Kualitas Pelayanan, dan Iklan Sosial Media Terhadap Customer Engangement - Lestari, Yuli Dewi; Violinda, Qristin; Setyorini, Noni (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of Customer Relationship Management (CRM), service quality, and social media advertising on customer engagement among consumers at Ayuri Homedress in Kayen District, Pati Regency. Facing competition in the fashion industry, it is crucial for businesses to build strong relationships with customers to create sustainable engagement. This study employed a quantitative approach, using a survey method using a questionnaire distributed to 96 respondents, selected using a purposive sampling technique. Data analysis was performed using multiple linear regression using SPSS software. The results indicate that, both partially and simultaneously, the three independent variables—Customer Relationship Management, service quality, and social media advertising—have a positive and significant effect on customer engagement. These findings offer practical implications for businesses, particularly in maximizing CRM strategies, improving service quality, and optimizing the use of social media as a promotional tool to strengthen relationships with consumers.